Energy consumption reduction by multi-hop transmission in cellular network - Ngor, Pengty (2015)
Adding relay stations between base station and mobile stations in a cellular network can extend network coverage, overcome multi-path fading and increase the capacity of the system. With the increase of data traffic, more and more energy is needed to support communication. Hence, it is challenging to design an optimal relay network that minimizes the average energy consumption. In this paper, a 3-tier-chitecture with two-hop relay network consisting of a source, a destination and multiple relay nodes is proposed to decrease the consumed energy for a given QoS requirement.